Perceived Benefits, Harms, and Views About How to Share Data Responsibly: A Qualitative Study of Experiences With and Attitudes Toward Data Sharing Among Research Staff and Community Representatives in Thailand. (July 2015) - Cheah, Phaik Yeong; Tangseefa, Decha; Somsaman, Aimatcha; Chunsuttiwat, Tri; Nosten, François; Day, Nicholas P. J.; Bull, Susan; Parker, Michael
The Thailand Major Overseas Programme coordinates large multi-center studies in tropical medicine and generates vast amounts of data. As the data sharing movement gains momentum, we wanted to understand attitudes and experiences of relevant stakeholders about what constitutes good data sharing practice. We conducted 15 interviews and three focus groups discussions involving 25 participants and found that they generally saw data sharing as something positive. Data sharing was viewed as a means to contribute to scientific progress and lead to better quality analysis, better use of resources, greater accountability, and more outputs. However, there were also important reservations including potential harms to research participants, their communities, and the researchers themselves. Given these concerns, several areas for discussion were identified: data standardization, appropriate consent models, and governance.